Social Media Provocation and Public Opinion Shifts in Government Policy Evaluation: A PRISMA Systematic Review - Maharudin, Didy; Muliyati, Muliyati (Research Horizon, 2025)
The rapid growth of social media has changed how public opinion forms and evaluates government policies, often through provocative content that spreads quickly and creates strong emotional reactions. This systematic literature review examines how such provocation causes shifts in public opinion, especially in non-election periods and emerging democracies. The study uses the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) framework to analyze 25 high-quality studies published between 2021 and 2025, selected from 309 initial records across several databases. Results show that social media provocation has a moderate to large effect on opinion shifts, with negative sentiment toward government policies appearing in more than half of cases. Opinion changes follow three clear temporal phases within 72 hours: initial exposure, social amplification, and crystallization. TikTok and Twitter display the highest levels of provocation, while digital literacy strongly reduces individual vulnerability. These findings highlight the need for proactive digital governance and faster government responses. Current regulations and reactive strategies are often too slow to counter rapid provocation. The review recommends building strong media literacy programs, creating early-warning systems, and adjusting platform algorithms to limit outrage-driven content in order to protect democratic stability in the digital age.